Source apportionment of PM2. 5 in Beijing in 2004 - Yu Song; Xiaoyan Tang; Shaodong Xie; Yuanhang Zhang; Yongjie Wei; Zhang, Minsi; Limin Zeng; Sihua Lu (Journal of hazardous materials, 2007)
Based on measurements of fine particulate matter (PM2.5, i.e., particles with an aerodynamic diameter of 2.5 μm or less) in January and August 2004, serious air pollution persists in Beijing. The chemical analysis included organic and elemental carbon, water-soluble ions, and elemental compositions. The positive matrix factorization (PMF) method was used to apportion the PM2.5 sources. The sources contributing dominantly to PM2.5 mass concentrations are coal combustion in winter and the secondary products in summer. Furthermore, the contributions from motor vehicles, road dusts and biomass burning could not be neglected. The products of biomass burning for winter heating in the area around Beijing could enter the urban area during quasi-quiescent weather conditions. In conclusion, some effective control measures were proposed to reduce the PM2.5 pollution in Beijing.